2017
DOI: 10.1080/10408363.2017.1394267
|View full text |Cite
|
Sign up to set email alerts
|

The vascular endothelium: A regulator of arterial tone and interface for the immune system

Abstract: As the primary interface between the blood and various tissues of the body, the vascular endothelium exhibits a diverse range of roles and activities, all of which contribute to the overall health and function of the cardiovascular system. In this focused review, we discuss several key aspects of endothelial function, how this may be compromised and subsequent consequences. Specifically, we examine the dynamic regulation of arterial contractility and distribution of blood flow through the generation of chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 129 publications
1
55
0
4
Order By: Relevance
“…The ENT4 substrates adenosine and 5‐HT are prominent among these endogenous regulators. Dynamic regulation of local blood flow is generally attributed to vascular endothelial mechanisms, specifically NOS generated NO and K Ca channel‐mediated endothelial hyperpolarization (EDH; Kerr et al, 2012; Khaddaj Mallat, 2017). Thus, we assessed the relative contribution of NO and EDH mechanisms to the responses of isolated mesenteric arteries to the vascular regulators acetylcholine/methacholine, adenosine, and 5‐HT in both male and female WT and ENT4‐KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…The ENT4 substrates adenosine and 5‐HT are prominent among these endogenous regulators. Dynamic regulation of local blood flow is generally attributed to vascular endothelial mechanisms, specifically NOS generated NO and K Ca channel‐mediated endothelial hyperpolarization (EDH; Kerr et al, 2012; Khaddaj Mallat, 2017). Thus, we assessed the relative contribution of NO and EDH mechanisms to the responses of isolated mesenteric arteries to the vascular regulators acetylcholine/methacholine, adenosine, and 5‐HT in both male and female WT and ENT4‐KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sprouting angiogenesis, which drives the formation of new capillaries from pre-existing microvessels, is exacerbated in the retina, thereby resulting in retinopathy [9].An increase in intracellular Ca 2+ concentration ([Ca 2+ ] i ) is crucial to fine tune endothelial cell functions [10][11][12]. For instance, endothelial Ca 2+ signals drive the release of many vasodilators, including nitric oxide, prostacyclin, arachidonic acid metabolites and hydrogen sulfide, and recruit Ca 2+ -activated K + channels to stimulate endothelium-dependent hyperpolarization [13][14][15][16]. In addition, an increase in endothelial [Ca 2+ ] i leads to the production of the vasoconstrictor prostanoids, thromboxane A2, prostaglandin H2 and endothelin-1 [14,17,18].…”
mentioning
confidence: 99%
“…In addition, an increase in endothelial [Ca 2+ ] i leads to the production of the vasoconstrictor prostanoids, thromboxane A2, prostaglandin H2 and endothelin-1 [14,17,18]. Vasoactive agonists bind to specific G-protein coupled receptors to engage phospholipase Cβ, a membrane-bound enzyme that cleaves inositol-1,4,5-trisphosphate (InsP 3 ) from its precursor phosphatidylinositol-4,5-bisphosphate [14,15]. The following Ca 2+ response typically consists of an initial Ca 2+ peak, which is mediated by InsP 3 -induced Ca 2+ release from the endoplasmic reticulum (ER), followed by a prolonged influx of Ca 2+ , known as a plateau [19,20].…”
mentioning
confidence: 99%
“…Hypertension is a common health problem with a complicated pathophysiology. Recently it was found that the positive feedback loop comprising oxidative stress, inflammation, and endothelial dysfunction may play a key role in the pathogenesis and progression of hypertension . The cross‐talk between NO and H 2 S represents a promising field of research and has attracted a great deal of interest recently as the defect in NO/H 2 S homeostasis is involved in the pathogenesis of hypertension and has a strong influence on vascular tone regulation .…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a substantial health problem that results in cardiovascular remodelling and serious complications such as stroke and ischaemic heart disease . The pathophysiology of hypertension is very complicated and recent evidence suggests that the positive feedback loop comprising oxidative stress, inflammation, and endothelial dysfunction may play a crucial role in the pathogenesis and progression of hypertension …”
Section: Introductionmentioning
confidence: 99%